2009
DOI: 10.1007/s00066-009-1929-4
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclooxygenase-2 Inhibitor Nimesulide, a Nonsteroidal Analgesic, Decreases the Effect of Radiation Therapy in Head-and-Neck Cancer Cells

Abstract: Nimesulide differentially affects cell proliferation and clonogenic survival and may decrease the efficacy of radiotherapy. Short-term assays to assess tumor growth may not correctly predict the clinically relevant long-term effect of COX-2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…Furthermore, it has radiosensitizing properties in head and neck cancer cells. These results are more promising than the ones we could show using nimesulide, a cyclooxygenase-2 inhibitor, in combination with irradiation on HNSCC cells [3]. As a consequence, it would make sense to do further investigations on betulinic acid's capability in combination with other cancer treatment modalities in different types of tumor tissue and also investigating possible radioprotective abilities on normal tissue [22].…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, it has radiosensitizing properties in head and neck cancer cells. These results are more promising than the ones we could show using nimesulide, a cyclooxygenase-2 inhibitor, in combination with irradiation on HNSCC cells [3]. As a consequence, it would make sense to do further investigations on betulinic acid's capability in combination with other cancer treatment modalities in different types of tumor tissue and also investigating possible radioprotective abilities on normal tissue [22].…”
Section: Discussionmentioning
confidence: 75%
“…In one report, it has been shown that the selective COX-2 inhibitor nimesulide decreased radiation efficiency of two head-and-neck cancer cells lines (SCC9 and SCC25) which are COX-2 positive [139]. This suggests that the sensitization of tumor cells to radiation might be strongly dependent on tumor cell type.…”
Section: Cox-2 Inhibitors In Cancer Therapymentioning
confidence: 99%
“…In this regard, selective COX-2 inhibitors were recently reported to enhance the response of primary tumors to radiation in vitro and in vivo [30,32,33,35,37,40,52]. On the other hand, the COX-2 inhibitor nimesulide did not increase the radiation response of squamous cell carcinoma cells in vitro [5]. The therapeutic efficacy of a combination of COX-2 inhibition and radiation on secondary bone tumors has not been described so far.…”
Section: Introductionmentioning
confidence: 95%